Life and achievements of an hospital director: Enrico Ronzani - Fara, Gaetano Maria; RONZANI, ENRICO (Acta Biomedica Atenei Parmensis, 2020)
The paper illustrates the life and the achievements of Enrico Ronzani, born in Padua and graduated in Medicine at the Bologna University. He directed the hospitals of Florence and the Ospedale Maggiore of Milan, promoting its growth until it became the seat of the Medical School promoted by Prof Mangiagalli, and he himself became Full Professor of Hygiene. In such a position he taught Hygiene also to Architets and Engineers, built the new Institute of Hygiene and helped to design and build the new great Hospital of Niguarda. But, most of all, he was successful in designing, promoting and officializing the job of the Hospital Directors, which was subsequently recognized by the law; and, publishing a series of books on the role of the modern hospitals, he prefigured their position in a web of medical institutions to include also those devoted to pre- and post-hospital assistance to the population. Practically he foresaw what was realized many years later through the creation of the Italian National Health Service (Law 833 of 1978).